KOMPETENSI PEDAGOGIS GURU DALAM PENGEMBANGAN SOSIAL EMOSIONAL ANAK USIA DINI PADA GUGUS SEKOLAH 11 ARJOWINANGUN KOTA MALANG - rina rinawijayanti; muhammad akbar (Pedagogi : Jurnal Anak Usia Dini dan Pendidikan Anak Usia Dini, 2016)
This  study  was  conducted  to  determine  (1)  the  business  conducted  by  the  teacher  to provide  the  infrastructure  basis  for  development  of  social‐emotional  early  childhood  (2) the  learning  process  for  the  development  of  social‐emotional  already  implemented teacher  at  school  (3)  the  monitoring  and  evaluation  of  development  capabilities  social‐emotional  early  childhood  teachers  in  the  school  have  been  implemented.  This  study  uses a  qualitative  case  study  method,  and  Spradley  models  using  analytical  techniques.  Based on the research conducted, the research aspects of the provision of infrastructure facilities basic  social  development  emotional  early  childhood  are:  (1)  teachers  do  not  have  a description of the tools for social development emotional early childhood, (2) development of social skills emotional early childhood was centered on the teacher, (3) emotional social learning  tools  that  have  not  been  revitalized.  In  the  aspect  of  the  process  and  strategy  for the  establishment  of  social  and  emotional  learning,  is  only  focused  on  imitation  and habituation  and  there  has  been  no  specific  program  of  habituation  behavior  with  the specific  objective  of  social  aspects  of  emotional  development  of  young  children.  While  the monitoring  and  evaluation  aspects:  (1)  monitoring  and  evaluation  efforts  are  not  focused on  the  child,  but  the  ending  or  the  result  of  imitation  that  has  been  done,  (2)  monitoring and  evaluation  of  social  emotional  learning  only  at  the  end  or  summarize  the  behavior  of pupils.  (3)  psikotes  AUD  never  become  reference  material  preparation of  the  learning program.  (4)  monitoring  and  evaluation  of  social  emotional  learning  only  take  place  if there are obstacles or disputes pupil.